2009
DOI: 10.1182/blood.v114.22.5098.5098
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Levels Are Associated with Vascular Damage in Patients with Nonalcoholic Fatty Liver Disease.

Abstract: 5098 Background and Aims Increased ferritin and body iron stores are frequently observed in nonalcoholic fatty liver disease (NAFLD), associated with heightened susceptibility to vascular damage. Conflicting data have been reported on the role of iron in atherosclerosis, with recent data suggesting that excess iron induces vascular damage by increasing levels of the hormone hepcidin, which would determine iron trapping into macrophages, oxidative stress, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In 143 patients with non-alcoholic fatty liver disease, hepcidin-25 levels were found to be associated with the presence of carotid plaques. 18 In a similar group of 130 patients with nonalcoholic fatty liver disease, monocyte chemo-attractant protein-1, a chemokine that plays an important role in both the initiation and progression of atherosclerosis, was 0.8737 ± 0.1956 BMI = body mass index; CIMT = carotid intima media thickness; CRP = C-reactive protein; CVD = cardiovascular disease; DBP = diastolic blood pressure; ESA = erythropoesis stimulating agent; HDL = high-density lipoprotein; LDL = low-density lipoprotein; RAS = renin angiotensin system; SBP = systolic blood pressure; TSAT = transferrin saturation.…”
Section: Discussionmentioning
confidence: 99%
“…In 143 patients with non-alcoholic fatty liver disease, hepcidin-25 levels were found to be associated with the presence of carotid plaques. 18 In a similar group of 130 patients with nonalcoholic fatty liver disease, monocyte chemo-attractant protein-1, a chemokine that plays an important role in both the initiation and progression of atherosclerosis, was 0.8737 ± 0.1956 BMI = body mass index; CIMT = carotid intima media thickness; CRP = C-reactive protein; CVD = cardiovascular disease; DBP = diastolic blood pressure; ESA = erythropoesis stimulating agent; HDL = high-density lipoprotein; LDL = low-density lipoprotein; RAS = renin angiotensin system; SBP = systolic blood pressure; TSAT = transferrin saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in separate studies using similar cohorts of Italian NAFLD subjects, Valenti et al have shown that the C282Y/WT and H63D/H63D genotypes were independently associated with HC iron deposition using multivariate regression analysis, 32 and that these combined genotypes had lower serum hepcidin levels than subjects with either H63D/WT or WT/WT genotypes with similar SF levels. 31 All known C282Y homozygotes were excluded from all NASH CRN studies, thereby not allowing us to determine the effect of C282Y homozygosity on hepcidin level, degree of hepatic iron deposition, or relationship to NAFLD severity. However, the degree of penetrance of C282Y heterozygosity to cause mild to moderate HC iron loading in NAFLD subjects (34%) appears to be similar to the penetrance of C282Y homozygosity to cause HC iron overload in HH patients; an estimated 38%-50% of C282Y homozygotes develop iron overload (33), with 1%-28% developing iron-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this group was described previously. 18 Hepatic iron staining was performed according to Scheuer,16 in patients from a previous study or when hyperferritinaemia or NASH were present. 13 Hepatic iron quantification by atomic absorption spectrometry was performed in 129 patients.…”
Section: Validation Cohortmentioning
confidence: 99%